PENGARUH KOMPETENSI, MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA APARATUR SIPIL NEGARA KANTOR PENCARIAN DAN PERTOLONGAN MAKASSAR - Suriadiningrat Palembai; Muhammad Rusydi Rahman; Edi Jusriadi (COMPETITIVENESS, 2020)
This study aims to find out and analyze the influence of competence, motivation and leadership on the Performance of State Civil Apparatus (ASN) Makassar Search and Rescue Office and know and analyze the variables that predominantly affect the performance of ASN Makassar Search and Rescue Office. The research has been conducted at the Makassar Search and Rescue Office with an implementation time of 2 months, namely from April to May of 2020 with a sample of 99 people. The analysis method used in this research is quantitative descriptive method, through regression testing by conducting validity and reliability test of question items of each variable as well as assumption test. The results showed that Competency has a significant influence on performance with P = 0.0040.05 with a coefficient value of 0.338, this coefficient shows that the better the competency of ASN, the performance of ASN in Makassar Search and Rescue Office will increase; Motivation has a significant influence on performance with P = 0.0050.05 with a coefficient value of 0.295, this coefficient shows that the better the work motivation of ASN, the better performance will be; Leadership has no significant influence on performance with P = 0.1980.05 with a coefficient value of 0.122, this coefficient shows that the leadership applied to the Makassar Search and Rescue Office has not been able to improve employee performance; and the variable that has the dominant effect on performance is competency, this can be seen from the beta value of 0.346 greater than other variables.Keywords: Competence, motivation, leadership and performance